Analysis of Marketing Channels And Marketing Efficiency of Corn Farmers (Zea Mays L) Tanjung Morawa - Riris Nadia Syafrilia Gurning; Nurhajijah Nurhajijah; Salsabila Salsabila; Sakral Hasby Puarada; Wildani Lubis (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aims to (1) identify the corn marketing channels, (2) determine the corn marketing margins, and (3) evaluate the efficiency of corn marketing in Tanjung Morawa District. Methodology: A sample of 30 corn farmers from three villages with corn farming areas was selected. A quantitative descriptive analysis was used to examine marketing channel patterns and analyze marketing costs and margins. Results: The study found that Marketing Channel I is widely used by farmers, who prefer selling corn directly to collectors. The marketing efficiency values for the first (I) and second (II) marketing channels are 10% and 16.6%, respectively. Findings: Both marketing channels are efficient. This indicates that the marketing channels involved in the marketing of shelled corn in the study area do not involve lengthy marketing institutions, resulting in low marketing costs and margins, and the selling price received by the final consumer is not much higher than the price received by the farmers. Novelty: This research provides insights into the efficiency of corn marketing channels, highlighting the benefits of shorter marketing pathways. Originality: The study offers a detailed analysis of marketing channel efficiency for corn, contributing to the understanding of effective agricultural product marketing. Conclusions: The corn marketing channels in Tanjung Morawa District are efficient, benefiting both farmers and consumers. Type of Paper: Empirical Research Article